Perlindungan Hukum Terhadap Korban Pelecehan Seksual Verbal (Catcalling) di Kota Tidore Kepulauan - Yuslan, Anggreni M; Hamid, Hasmiah; Lego, Indra Rusdian (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study examines the legal protection provided to victims of verbal sexual harassment (catcalling) in Tidore Islands City and the factors influencing the low level of public legal awareness. Catcalling, as a form of non-physical sexual harassment, is an act that demeans the victim's dignity and is regulated as a criminal offense under Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence, the Criminal Code, and other regulations. This study employed an empirical legal research method with an empirical juridical approach. Primary data were collected through interviews with the Women and Children's Service Unit (PPA) of the Tidore Police and catcalling victims, as well as secondary data from literature and laws and regulations. The results indicate that legal protection for catcalling victims in Tidore Islands City has been implemented optimally and in accordance with applicable legal provisions. Law enforcement officers, through the PPA Unit of the Tidore Islands Police, provide protection from receiving reports, assisting victims, conducting investigations, and handling them, guided by the TPKS Law and the Witness and Victim Protection Law. Despite this, the number of official reports remains low, not due to weaknesses in the legal system, but rather to social and psychological factors within the community. Factors influencing low public legal awareness include a strong patriarchal culture, the perception that catcalling is commonplace, a lack of understanding of victims' rights, and fear and shame in reporting it. This situation indicates that although legal protection is available and implemented according to regulations, public understanding of the law still needs to be improved. Therefore, more widespread and intensive legal education is needed to ensure the public understands that catcalling is a criminal offense and that victims have the right to protection.